Forecasting Air Temperature Using the Triple Exponential Smoothing Method - Heri Susanto; Dimara Kusuma Hakim (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2024)
Changes in air temperature are a major challenge in Indonesian agriculture. Erratic air temperatures hurt plant growth, so farmers must adjust planting schedules and plant selection according to the air temperature at a certain period. The author aims to predict minimum and maximum air temperatures in Temanggung district in 2024 using the Triple Exponential Smoothing (TES) method. Monthly air temperature data in Temanggung district for the period 2020 to 2023 is used for air temperature forecasting using the TES method. The analysis results show that the TES model can predict air temperature with fairly good accuracy. The minimum temperature is expected to be 23°C, maximum 26-27°C. The research results provide benefits for the agricultural sector in Temanggung. Farmers can use the results of air temperature predictions to adjust planting schedules based on crops that suit the air temperature to minimize the negative impact of air temperature on plant growth and agricultural yields.